1993
DOI: 10.1177/0893318993006003002
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Ambiguity in the Birth of a Loosely Coupled Organization

Abstract: The processes surrounding the birth of organizations have been explained on the basis of structural contingency, resource dependency, population ecology, and institutional theories. In general, these theories view the role of communication and interpretation as largely unproblematic. We argue that strategically ambiguous messages play a key role in the birth of loosely coupled organizations. The successful birth is contingent on these messages being interpreted differently by key constituencies in the organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Thus, the actual content of strategy texts will be influenced by the micro-level translation process itself. For example, several studies have suggested that difficulties in translation may be resolved by a form of 'strategic ambiguity' (Eisenberg, 1984) in which written texts remain open to alternative interpretations, allowing a variety of stakeholders to accept them (Abdallah, 2007;Contractor & Ehrlich, 1993;Tracy & Ashcraft, 2001). Although, this remains to be studied, one might also hypothesize that the juxtaposition of multiple interests in strategy texts would tend to increase the complexity of narrative plots and potentially reduce their coherence.…”
Section: Narrative and Strategy Textsmentioning
confidence: 99%
“…Thus, the actual content of strategy texts will be influenced by the micro-level translation process itself. For example, several studies have suggested that difficulties in translation may be resolved by a form of 'strategic ambiguity' (Eisenberg, 1984) in which written texts remain open to alternative interpretations, allowing a variety of stakeholders to accept them (Abdallah, 2007;Contractor & Ehrlich, 1993;Tracy & Ashcraft, 2001). Although, this remains to be studied, one might also hypothesize that the juxtaposition of multiple interests in strategy texts would tend to increase the complexity of narrative plots and potentially reduce their coherence.…”
Section: Narrative and Strategy Textsmentioning
confidence: 99%
“…. ] gives room for alternative reactions to the same piece of language (Empson, 1949, p. 1). In Seven Types of Ambiguity, Empson (1949) sets the pattern for making sense of strategic ambiguity (SA) (Contractor and Ehrlich, 1993;Eisenberg, 1984) or the intentional use of equivocation (Bavelas et al, 1990;Eisenberg, 1998) to achieve desired ends within organizations and networks. Empson's influence surpassed the borders of literary criticism ( Jancovich, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As Wexler (2009) suggested, the various combinations of sustainability elements (people, profit, and planet) create imprecision, lack of specificity, and operational indices that lead people to believe that they are far better off joining a coalition than going it alone. An ambiguous but inclusive organizational mission statement that is mutually agreed upon could help different university departments to put aside their differences and make efforts to pursue the same goal (Contractor & Ehrlich, 1993).…”
Section: Role Of Ambiguity Logic In Institutional Complexitymentioning
confidence: 99%
“…Thus, ambiguity is associated with the sharing of power among stakeholders, that is, in making power more equally distributed among stakeholders. In other cases, the use of the ambiguity strategy was usually found among relatively more power-symmetric relationships between management and other stakeholders, such as university academics (Contractor & Ehrlick, 1993; Jarzabkowski & Sillince, 2007; Jarzabkowski, Sillince, and Shaw, 2010; Sillince et al, 2012), medical doctors in hospitals (Denis et al, 2011), and film producers and makers (Abdallah & Langley, 2014). These professionals possess relatively more power over management compared to other kinds of employees because of their valuable knowledge and skill background.…”
Section: Role Of Ambiguity Logic In Institutional Complexitymentioning
confidence: 99%